Exome Sequencing Reveals Genetic Variability and Identifies Chronic Prognostic Loci in Chinese Sarcoidosis Patients - Zhang, Qian; Huang, Hui; Zhang, Meijun; Fang, Chuling; Wang, Na; Jing, Xiaoyan; Guo, Jian; Sun, Wei; Yang, Xiaoyu; Xu, Zuojun (Frontiers in Oncology, 2022)
Background: Sarcoidosis is an inflammatory disease characterized by noncaseating granuloma formation in various organs, with several recognized genetic and environmental risk factors. Despite substantial progress, the genetic determinants associated with its prognosis remain largely unknown. Objectives: This study aimed to identify the genetic changes involved in sarcoidosis and evaluate their clinical relevance. Methods: We performed whole-exome sequencing (WES) in 116 sporadic sarcoidosis patients (acute sarcoidosis patients, n=58; chronic sarcoidosis patients, n=58). In addition, 208 healthy controls were selected from 1000 G East Asian population data. To identify genes enriched in sarcoidosis, Fisher exact tests were performed. The identified genes were included for further pathway analysis using Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG). Additionally, we used the STRING database to construct a protein network of rare variants and Cytoscape to identify hub genes of signalling pathways. Results: WES and Fisher’s exact test identified 1,311 variants in 439 protein-coding genes. 135 SNPs on 30 protein-coding genes involved in the immunological process based on the GO and KEGG enrichment analysis. Pathway enrichment analysis showed osteoclast differentiation and cytokine–cytokine receptor interactions. Three missense mutations (rs76740888, rs149664918, and rs78251590) in two genes (PRSS3 and CNN2) of immune-related genes showed significantly different mutation frequencies between the disease group and healthy controls. The correlation of genetic abnormalities with clinical outcomes using multivariate analysis of the clinical features and mutation loci showed that the missense variant (rs76740888, Chr9:33796673 G>A) of PRSS3 (P=0.04, odds ratio [OR]= 2.49) was significantly associated with chronic disease prognosis. Additionally, the top two hub genes were CCL4 and CXCR4 based on protein–protein interaction (PPI) network analysis. Conclusion: Our study provides new insights into the molecular pathogenesis of sarcoidosis and identifies novel genetic alterations in this disease, especially PRSS3, which may be promising targets for future therapeutic strategies for chronic sarcoidosis.